2020
DOI: 10.9734/cjast/2020/v39i4531156
|View full text |Cite
|
Sign up to set email alerts
|

Review on IoT Based Precision Irrigation System in Agriculture

Abstract: Precise irrigation plays an essential role in agricultural production and its management. Based on current conditions and historical records, profitability in the farming sector depends on making the right and timely operational decision. For the last two decades, especially in India, climate change, groundwater depletion, and erratic variation in rainfall have affected crop production significantly.  Due to advancements in technologies and reduction in size, sensors are becoming involved in almost every field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The field data collection system contains three sensors: a capacitive soil moisture sensor (v2.0), a soil temperature sensor (DS18B20), and a temperature and humidity sensor (DHT11). The output of this sensor is read by an ESP32-WROOM-32 microcontroller, which wirelessly transmits the recorded data to an IoT platform (ThingSpeak) using an ESP8266 Wi-Fi module (Kumar et al 2020;Kumar et al 2022;Kumar et al 2023). Details of the development of IoT-based smart drip irrigation systems are described in (Kumar et al 2022;Kumar et al 2023), and a flowchart of the process is shown in (Fig.…”
Section: Iot-based Data Acquisition Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The field data collection system contains three sensors: a capacitive soil moisture sensor (v2.0), a soil temperature sensor (DS18B20), and a temperature and humidity sensor (DHT11). The output of this sensor is read by an ESP32-WROOM-32 microcontroller, which wirelessly transmits the recorded data to an IoT platform (ThingSpeak) using an ESP8266 Wi-Fi module (Kumar et al 2020;Kumar et al 2022;Kumar et al 2023). Details of the development of IoT-based smart drip irrigation systems are described in (Kumar et al 2022;Kumar et al 2023), and a flowchart of the process is shown in (Fig.…”
Section: Iot-based Data Acquisition Systemmentioning
confidence: 99%
“…Due to the wiring connection range, such systems have a limited deployment size for monitoring points; they require extensive cabling, which leads to high installation, maintenance, and relocation costs; and the cables are easily damaged if placed outdoors in adverse conditions (Kumar et al 2020;Kumar et al 2022;Kumar et al 2023). In the present research work, we have developed an IoT system that uses wireless sensor networks (WSNs) technology to overcome previous wired sensor system issues.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to automate irrigation with the aid of contemporary technology and reap the benefits of increased output, reduced water use, and reduced soil erosion, among other things. S. Vinod Kumar et al (2020) [19] IoT-based smart irrigation has been examined in this article. The Internet of Things (IoT) platform can substitute for the lack of agricultural labour in irrigation.…”
Section: Iot Based Smart Irrigation System For the Betterment Of The ...mentioning
confidence: 99%
“…These are not the only problems; it is also clear that interest in agriculture and its development has decreased in some developing countries, as in the case of Latin America, where in countries such as Colombia, the future possibilities of farming are not clear, and the population is migrating to the big cities. This migration is not unique to this continent; it can be seen in other countries, as in the case of India, where it is becoming a more materialized reality every day [4]. Therefore, the Ministry of Science and Technology of Colombia (MinCiencias) has mentioned in the 2017 working document on the SDGs and the contribution of science, technology, and innovation (STI), that a successful contribution to the SDGs is not a simple effort of academia and its research groups, but that efforts must be in conjunction with several factors such as civil society, industry and, of course, the government [5].…”
Section: Introductionmentioning
confidence: 99%